Pengaruh Literasi Keuangan, Penggunaan E-Money Dan Pengendalian Diri Terhadap Perilaku Konsumtif Mahasiswa Akuntansi Di Kota Batam - Light, November Twenty Light; Poniman, Poniman (SCIENTIA JOURNAL, 2024)
Consumptive behavior is the act of consuming an item or service excessively with high intensity that tends toprioritize wants over needs. The study aims to determine the effect of financial literacy, e-money usage, and selfcontrol on the consumptive behavior of accounting students in Batam city. The total population was 1,354accounting students with a sample of 93 accounting students. This study uses a quantitative approach with simplerandom sampling technique using primary data obtained from distributing questionnaires online using googleform. The data in this study were processed using SPSS (Statistical Package for Social Science) software version26. The data analysis technique in this study used validity test, reliability test, classical assumption test andhypothesis testing. The results of the t test research explain that financial literacy and the use of e-money partiallyhave no effect on the consumptive behavior of accounting students. Self-control partially affects the consumptivebehavior of accounting students. The results of the F test research explain that financial literacy, e-money usage,self-control simultaneously have a significant effect on the consumptive behavior of accounting students with apercentage of 17.9% and the remaining 82.1% is influenced by other variables.